Shakespeare’s Conspiracy Theorist: Richard III in the Context of Thomas Hobbes’ State of Nature - Özata, Cüneyt (Journal of History Culture and Art Research, 2020)
Thomas Hobbes disagreed with the ideas of previous thinkers about the existence of the state in the history of political philosophy, which made progress in the 17th century and made its way to the Age of Reason. He argues that humanity exists in a 'state of nature' when it is not a state and explains it in his work Leviathan. Most of the characters in Shakespeare's play Richard III have traces of Hobbes' concept of the natural state. As with many other characters created by Shakespeare for his plays prior to and following the publication of Richard III, the characters in this play seem to be either goal-oriented, with certain motives to carry out, or rather ignorant of the actions happening around them only to learn about them too late. The goals of the former characters and what they accomplish for these purposes are similar to those of Hobbes in terms of state and power. In particular, the conspiracies and theories that Richard's character has established reveal the state of nature and the impasse for a society that experiences an absence of power. In this study, Richard III, one of the earliest plays and the most controversial works of Shakespeare at the beginning of the Renaissance period, is analysed in the light of Hobbes' ideas. Within this context, a thorough examination of the play with regards to the actions and the statements made by the characters was conducted to prove the existence of Hobbes’ ideas as integrated into the play. The conclusion drawn is that the study indicated strong inclusion of Hobbes’ state of nature idea in the play as the tenets of the said idea is abundant throughout the work. Being a political playwright as well as a philosophy-driven writer, Shakespeare can be said to have employed Hobbes’ ideas and moulded them into living and breathing characters to show the possible calamities an absence of power may entail.